2022
DOI: 10.1177/10731911221127902
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Empathy Across the Adult Lifespan: A Comparison of Three Assessment Types

Abstract: Empathy is a core component of social cognition that can be indexed via behavioral, informant-report, or self-report methods of assessment. However, concerns have been raised regarding the lack of convergence between these assessment approaches for cognitive empathy. Here, we provided the first comparison of all three measurement approaches for cognitive and affective empathy in a large adult sample ( N = 371) aged 18 to 101 years. We found that poor convergence was more of a problem for cognitive empathy than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, these prior studies relied on self-report measures for both physical activity and emotional intelligence, whereas in our study, objective measures were used to assess both CRF and social cognition. Prior work has shown that self-report measures do not correlate strongly with objective measures for physical activity or social cognition (see Grainger et al, 2023b ; Prince et al, 2008 ), therefore differences in measurement type might explain the discrepancy in findings. Indeed, a meta-analysis examining the relationship between emotional intelligence and health reported larger correlations for self-report compared to objective measures of emotional intelligence ( Martins et al, 2010 ).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, these prior studies relied on self-report measures for both physical activity and emotional intelligence, whereas in our study, objective measures were used to assess both CRF and social cognition. Prior work has shown that self-report measures do not correlate strongly with objective measures for physical activity or social cognition (see Grainger et al, 2023b ; Prince et al, 2008 ), therefore differences in measurement type might explain the discrepancy in findings. Indeed, a meta-analysis examining the relationship between emotional intelligence and health reported larger correlations for self-report compared to objective measures of emotional intelligence ( Martins et al, 2010 ).…”
Section: Discussionmentioning
confidence: 91%
“…A limitation is that the MEQ was validated with selfreports only. Additionally, self-report methods in general are unlikely to capture actual differences in ability as shown as a lack of convergent validity between self-reports and other methods [74][75][76][77][78]. Therefore, we recommend that all mentalizing questionnaires showing good parametric values should be tested on the RF Scale to determine their validity.…”
Section: Limitations and Perspectivementioning
confidence: 99%
“…Third, in testing criterion validity, we assumed that measures of mindreading ability should be uniquely related to psychosocial functioning, however, it could be that this is only true for some individuals under certain circumstances (e.g., interaction effects). Fourth, we used a broad selection of self-report measures to assess impairments in psychosocial functioning, but informant reports (see, e.g., Grainger et al, 2022) or expert ratings by mental health professionals are another important source that could result in different conclusions.…”
Section: Limitationsmentioning
confidence: 99%